2014
DOI: 10.3329/jme.v43i2.17832
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Evaluation of Fiber Reinforced Polypropylene Thermoplastics for Aerospace Applications

Abstract: Fiber reinforced thermosetting composites have wide scope in the field of Aerospace and MilitaryApplications. These materials exhibit high strength and high stiffness, besides these composites have long fatiguelife, corrosion resistance, environmental stability, thermal insulation and conductivity. Researchers areexploring possibilities to use natural fiber reinforced polymer composites (NFRPCs) in response to the increasingdemand for environmentally friendly materials and also to develop reusable fiber reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Since China is leading in global primary energy consumption, it has become one of the largest CO 2 emitter countries, thereby contributing 27.6% of global emissions in 2017 [27]. However, to reduce its share in the world's GHG emissions, China has established the goal to increase its energy consumption to 20% of renewable energy sources by the year 2030 [30]. This can significantly reduce CO 2 emissions per unit GDP (Gross Domestic Product) by 60 to 65% [30,31].…”
Section: Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since China is leading in global primary energy consumption, it has become one of the largest CO 2 emitter countries, thereby contributing 27.6% of global emissions in 2017 [27]. However, to reduce its share in the world's GHG emissions, China has established the goal to increase its energy consumption to 20% of renewable energy sources by the year 2030 [30]. This can significantly reduce CO 2 emissions per unit GDP (Gross Domestic Product) by 60 to 65% [30,31].…”
Section: Energy Consumptionmentioning
confidence: 99%
“…However, to reduce its share in the world's GHG emissions, China has established the goal to increase its energy consumption to 20% of renewable energy sources by the year 2030 [30]. This can significantly reduce CO 2 emissions per unit GDP (Gross Domestic Product) by 60 to 65% [30,31].…”
Section: Energy Consumptionmentioning
confidence: 99%
“…Fig. 4 shows materials usage of new generation Boeing 787 aircraft, it is easy to find that consumption of composite materials is more than 50% [8] . It reported that Boeing 787 aircraft will reduce fuel consumption by 20%, 8% of that contributes to use composite materials extensively on aircraft.…”
Section: New Materials In Aircraftmentioning
confidence: 99%
“…Although thermoplastic composites were extensively characterized under quasistatic tensile, compressive, shear, and fatigue loading conditions [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], few studies concerned the dynamic mechanical behavior of thermoplastic composites at elevated temperatures. Thermoplastic composites are significantly sensitive to temperature.…”
Section: Introductionmentioning
confidence: 99%